Determinants of Corporate Risk Disclosure in Annual Reports of UK Companies - Ramakrishnappa, Paramesh (2009)
The dissertation was focused on understanding the determinants of corporate risk disclosure in annual reports of UK companies. There were three key objectives to the research: (1) evaluate the determinants of narrative disclosure concerning risk management and internal control in the UK companies that is valuable to policy makers, (2) explain how companies disclose their financial information to various stakeholders – users, employees, government and clients among others, and (3) evaluate the knowledge resulting from the research and identify hints for future regulation and provide an impetus for more empirical research.